2023
DOI: 10.1002/tpg2.20394
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide dissection and haplotype analysis identified candidate loci for nitrogen use efficiency under drought conditions in winter wheat

Ahossi Patrice Koua,
Md. Nurealam Siddiqui,
Katrin Heß
et al.

Abstract: Climate change causes extreme conditions like prolonged drought, which results in yield reductions due to its effects on nutrient balances such as nitrogen uptake and utilization by plants. Nitrogen (N) is a crucial nutrient element for plant growth and productivity. Understanding the mechanistic basis of nitrogen use efficiency (NUE) under drought conditions is essential to improve wheat (Triticum aestivum L.) yield. Here, we evaluated the genetic variation of NUE‐related traits and photosynthesis response in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Nitrogen is essential for plant growth and productivity, and understanding the mechanistic basis of nitrogen use efficiency (NUE) under drought conditions is crucial for improving crop yield. Through GWAS analysis, Koua et al (2023) identified 27 QTLs strongly linked to drought-related traits and 10 QTLs associated with NUE traits in wheat. Chromosomes 1B and 5A were found to harbor pertinent genomic loci containing potential genes such as amino acid transporters and cold shock proteins, with pleiotropic effects on enhanced NUE under drought stress.…”
Section: Drought Tolerancementioning
confidence: 99%
“…Nitrogen is essential for plant growth and productivity, and understanding the mechanistic basis of nitrogen use efficiency (NUE) under drought conditions is crucial for improving crop yield. Through GWAS analysis, Koua et al (2023) identified 27 QTLs strongly linked to drought-related traits and 10 QTLs associated with NUE traits in wheat. Chromosomes 1B and 5A were found to harbor pertinent genomic loci containing potential genes such as amino acid transporters and cold shock proteins, with pleiotropic effects on enhanced NUE under drought stress.…”
Section: Drought Tolerancementioning
confidence: 99%